Feminisme Eksistensialis dalam Cerpen Perempuan Yang Menikahi Tubuhnya Sendiri Karya M. Rifdhal Ais Annafis: Perspektif Simone De Beauvoir - Nora Erika Aulia; Agik Nur Efendi (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
The meaning of freedom for a woman does not only include equality in terms of work, opinion, or decision-making, but also the right to live free from patriarchal views, sexual violence, and subordination. Existentialist feminism presents as a critique of patriarchal domination and the labeling of the other or